Ambient air pollution and cardiovascular diseases: From bench to bedside. (May 2018) - Vidale, Simone; Campana, Carlo
Air pollution has a great impact on health, representing one of the leading causes of death worldwide. Previous experimental and epidemiological studies suggested the role of pollutants as risk factors for cardiovascular diseases. For this reason, international guidelines included specific statements regarding the contribution of particulate matter exposure to increase the risk of these events. In this review, we summarise the main evidence concerning the mechanisms involved in the processes linking air pollutants to the development of cardiovascular diseases.